Perceiving is believing: Understanding public preferences for dairy cow management in the UK - Jackson, Amy (2022)
Economic pressures imposed on the dairy industry since the mid-20th century have resulted in intensification at farm level, with expansions in herd size, increases in milk yield and the uptake of technology. However, this has moved dairy farming, and specifically the care of the dairy cow, out of alignment with public values, risking both future dairy consumption and social licence to operate. Understanding how the public perceive dairy farming and prefer the dairy cow to be managed would provide the dairy industry with opportunities to improve engagement and adapt systems to better meet societal expectations, thereby building a more secure future. First insights came from novel use of the discrete choice method ‘best worst scaling’ within a quantitative survey of 2,054 UK citizens, described in Chapter 2, which provided a scaled ranking by importance of 17 different attributes associated with dairy cow management and milk production. Through hierarchical Bayesian analysis, grazing, cow comfort and health & welfare were established as the three equal top priorities for the sample. However, these belied six underlying and characteristically distinct ‘citizen groups’, identified through latent class analysis and multinomial logistic modelling. Each group had very different preferences, suggesting significant diversity of preference for dairy cow management within the wider UK population. While the discovery of this diversity was novel, it did not explain the understandings the preferences were based on, or why. Therefore, from this, further aspects of public perceptions and preferences were explored in more detail through analysis of qualitative data. As described in Chapter 3, this was collected from face-to-face interviews with a subset of 60 participants from the sample in Chapter 2. The study described in Chapter 4 used mixed methods analysis of these data to determine public preferences for three dairy farming systems with differing access to pasture. Through integrating the results of reflexive thematic and linguistic analysis, strong preferences were established for a mixed system, grazing cows in summer and housing them in winter; this system matched a ‘dual vision’ of the cow’s domesticity and wildness, but was also shown to generate most confidence and positive emotion. The fully housed system was rejected by most, failing to meet the cow’s ‘wild’ persona and giving rise to negative emotions and denial. By contrast, the fully grazed system appeared aspirational, but its lack of protection produced linguistic discrepancies, signalling doubt. In conclusion, the mixed system best delivered the naturalness and care participants wanted. However, a lack of knowledge of the cow’s needs meant participants also deferred to others to choose, including the cow herself. Recognising that people process new information through interpretive lenses or ‘frames’ formed from memories and experiences, frame analysis of the qualitative data, as described in Chapter 5, indicated how the public might perceive dairy farming, and therefore how they might understand care of the cow. Through inductive thematic analysis, three frames developed for the cow presented her as enduring, a fellow, and a force of nature. Two frames described the farmer as traditional or modernising, but through positive and negative narratives which depended on the treatment of the cow, causing confusion about what actually happened on-farm. Reflecting on the impact of the frames, the evident connection participants felt with the cow explained public interest in her wellbeing; confusion about the motives of the farmer indicated a need for more overt illustrations of care. ‘Natural’ is an aspiration many have for the lives of farm animals – yet the term remains broad and ill-defined. Therefore, what people mean by ‘naturalness’ in dairy farming was explored in Chapter 6 by first identifying what participants deemed natural (or unnatural) by applying an adapted framework to the qualitative data, then reflexive thematic analysis to explain these perceptions. A wide range of topics including farmer behaviour, use of technology, and familiarity or normalcy indicated naturalness or unnaturalness; these were explained by the need for the cow to ‘be cow’; discomfort with excess; and the accountability of the farmer. Context determined whether ‘natural’ was actually detrimental, or ‘unnatural’, beneficial. The application of novel methods within this research has added new depth to understandings and fresh insight into public perceptions about dairy cow management in the UK. The findings offer opportunities to change how dairy farming practices are communicated, and to consider how dairy systems can be adapted to better meet changing societal needs.